(untitled) (Torani Journal of Fisheries and Marine Science, 2018)
As a filter feeder, windowpane oyster, Placuna placenta, which lives as a sedentary animal is very appropriate to be used as an eco-sentinel organism in marine bio-monitoring campaign. The study of lead (Pb) content in the tissue and shell of P. placenta was conducted in coastal waters of Mandalle, Pangkajene Kepulauan District, South Sulawesi. A hundred of oysters were collected from coastal waters of Mandalle. Morphometry parameters which were length, high, width, and dry weight of tissue were measured in the laboratory. Those parameters were used for determination of Condition Index (CI). Metal was analyzed by Atomic Absorption Spectrometry. The results showed that the contents of Pb in tissue and shell were 0.021 and 0.014 mg/kg DW (dry weight) respectively. The concentration of Pb in tissue was not overreach by BPOM 2009 Number Hk.00.06.1.52.4011 of 1.5 mg / kg DW (dry weight). After calculating Maximum Tolerable Intake (MTI), we found that MTI was 7.79 kg/day. In terms of marine monitoring campaign, we can theoretically use the CI as a morphological biomarker. After calculating the relationship between Pb in tissue and shell, we found that the value of CI was not correlated significantly with Pb content in tissue and shell. However, the correlation coefficient between Pb in tissue and CI was stronger than that in the shell. The potential of CI of windowpane oyster as a morphological biomarker was discussed. Keywords: Placuna placenta, lead, MTI, morphological biomarker